Thermal characteristics of dry cooling tower reconstructed from obsolete natural draft wet cooling tower and the relevant thermal system coupling optimization. (25th June 2020) - Ge, Wenjing; Zhao, Yuanbin; Song, Shiwei; Li, Wendong; Gao, Shasha; Chen, TieFeng
Highlights: Feasibility of reconstructing wet cooling tower into dry cooling tower is studied. One operation mode of reconstructed dry cooling system is presented and optimized. The established model for dry cooling system is validated based on literature data. Both water distribution schemes and some operation parameters are elaborated. Economic analysis for reconstructed dry cooling system is obtained. Abstract: Natural draft dry cooling tower is attractive in recent decades with its superiority of zero water loss. Some old thermal power plants are under high pressure of waste water reducing emission, thus the natural draft wet cooling tower is obsoleted. Reconstructing natural draft wet cooling tower into natural draft dry cooling tower is attractive for the saving of capital expenditure. But it has not been researched before, this study aims to fill this gap. Based on an actual reconstruction case, the operation mode of reconstructed dry cooling system is established and relevant MATLAB programming is realized, which is validated by literature data. The reconstructed system consists of two reconstructed natural draft dry cooling towers, a usual natural draft dry cooling tower and two 660 MW power units. The cooling capacity of reconstructed natural draft dry cooling tower is lower through thermal characteristic comparison with the usual natural draft dry cooling tower. In order to realize the optimal operation, different water distribution schemes are presented and several operation parameters are analyzed. Under the optimized reconstruction design, the annual water saving and annual cost are discussed. The annual water saving is about14.49 million metric tons that is about 8.86 million dollars and the minimum annual cost is about 181.47 million dollars, which brings great economic and environmental benefits.